The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1007/s11858-020-01165-7
|View full text |Cite
|
Sign up to set email alerts
|

Teaching with embodied learning technologies for mathematics: responsive teaching for embodied learning

Abstract: As technologies that put the body at the center of mathematics learning enter formal and informal learning spaces, we still know little about the teaching methods educators can use to support students' learning with these specialized systems. Drawing on ethnomethodology and conversation analysis (EMCA) and the CoOperative Action framework, we present three multimodal ways that educators can be responsive to learners' embodied ideas and help them transform sensorimotor patterns into mathematically significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…(2) using multimodal candidate understandings; and (3) coconstructing multimodally-expressed embodied ideas using gesture" (Flood et al, 2020).…”
Section: The Particular Challenges Of Dynamic Mathematical Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…(2) using multimodal candidate understandings; and (3) coconstructing multimodally-expressed embodied ideas using gesture" (Flood et al, 2020).…”
Section: The Particular Challenges Of Dynamic Mathematical Technologymentioning
confidence: 99%
“…The selected technology was the Mathematics Imagery Trainer for Proportions involving 23 Grade 4–6 school students from an urban school in the US state of California alongside four university mathematics education design researchers. The research concluded the following three ways in which educators can be responsive in such environments: “(1) explicitly encouraging learners to use gesture and being aware of gesture–speech mismatches; (2) using multimodal candidate understandings; and (3) co-constructing multimodally-expressed embodied ideas using gesture” (Flood et al, 2020 ).…”
Section: Concerning Classroom Practice—the Different and Emerging Plamentioning
confidence: 99%
“…Later, a tutor changes the task by asking the students to reflect on their sensory-motor strategies. As the tutors support the transition of sensory-motor experiences into mathematical discourse (Flood, 2018), they use a variety of multimodal tactics in eliciting students' verbal and gestural expressions of their sensory-motor coordinations and bridging these expressions with scientific discursive norms (Flood, 2018;Flood et al, 2020) 2 . Aiming to facilitate inclusion of sensory-motor coordinations into further mathematical reasoning in a course of embodied instrumentation (Drijvers, 2019), we supplemented embodied action-based design ideas by mathematical tasks that require instrumented actions.…”
Section: Empirical Illustration Of the Genesis Of A Body-artifact Functional Systemmentioning
confidence: 99%
“…-All Responsive teaching involves: 1) drawing out, attending to, and engaging with aspects of learners' ideas that have potential disciplinary value or substance; and 2) engaging in ongoing proximal formative assessment (e.g., continuously monitoring students' ideas to adapt instructional support in the moment) [Robertson et al (2016), Flood et al (2020), Flood et al (2022].…”
Section: Socio-emotionalmentioning
confidence: 99%